Synthesis and characterization of Cu₂Zn₁-xCdxSnS₄ quinternary alloy structure nanostructures using sol-gel electrospining technique
The principal aim of the research work presented in this thesis is to synthesise nanostructured Cu2Zn1-xCdxSnS4with different Cd concentrations (x=0 to 1)on glass, porous silicon (PS), oxidized silicon (SiO2) and GaN substratesusing different methods of spin coating and electrospinningtechniquesfor heterojunction, solar cell and Dengue type-2 DNA detector applications. In this work, we have studied the different effect copper (Cu) concentrations (0.3, 0.5, 0.7 and 0.9 mol/L) on the structural, morphological, optical and electrical properties of Cu2Zn0.8Cd0.2SnS4 quinternary alloy nanostructures prepared by spin coating technique. The direct band gap of Cu2Zn0.8Cd0.2SnS4quinternary alloy nanostructures decreases as Cu concentration increases from 1.81 eV at 0.3M to 1.60eV at 0.9M. The transmittance value in the range 63-49% was also dependent on Cu concentration. The refractive index and optical dielectric constant are calculated and gave good agreement with experimental and theoretical results. Electrical properties studied by Hall Effect measurement, showed ptype conductivity, with a carrier concentration between 7.819×1012 cm–3 and 3.76×1014 cm-3.It was observed a linear decreasing in the band gap of Cu2Zn1- xCdxSnS4/glassquinternary alloy nanostructures as Cd concentration increases.The transmittance value was 73% at x = 0 and 39% at x = 1. Hall Effect measurements suggest that all the grown nanostructures have p-type conduction. XRD results showed that Cu2Zn1-xCdxSnS4quinternaryalloy nanostructures has multiphase polycrystalline with preferential orientation along (112) and (312) directions with kesterite structure at x=0 and stannite structure at x=1.The Cu2Zn1-xCdxSnS4quinternary alloy nanostructures on PS (63.93%) substrate with different Cd concentration deposited via spin coating technique were successfully examined for heterojunction. The current-tovoltage (I-V) of Ag/n-PS/Cu2Zn1-xCdSnS4/Ag heterojunction at x= 0, 0.6, 1 was characterized. The photosensitivity increases as Cd concentration increases to of (3401.36) for x=0.6 compared with (282.40) for x=0 and (567.68) for x=1 respectively. Different method electrospinningtechnique is used to synthesise of Cu2Zn1- xCdxSnS4quinternaryalloynanofibres.